BreCaDS: Towards a Breast Cancer Decision Support System - Roxelle Garcia, April; Gerasmio, Ma. Beatrice; Tuastumban, Mae Lizza; Ababa, Milfe; Dimalen, Editha (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Breast cancer is a common disease worldwide. In Southeast Asia, the Philippines has the highest mortality rate making it one of the top ten breast cancer hot spots in the world. Stadies are conducted to identify if a person’s genetic makeup and environmental factor have something to do with the disease. One genetic factor is Human Epidermal Growth Factor Receptor-2 (HER2). This study developed a computer based decision support system (BreCaDS) that reveals a HER2 score which indicates if the cancer is aggressive or not through the given clinicopathological and cytological factors from pathology reports of breast invasive ductal carcinoma (BIDC) patients. The BreCaDS algorithm is based on the concept of pattern recognition and decision trees. Using 89 randomly picked data samples from breast cancer patients the system obtained a 75% reliability. This can aid clinicians in providing a better treatment course for breast cancer patients. BreCaDS is the first and pioneering study on breast cancer and HER2 on the Filipino population. It is recommended that with more data samples the reliability of the system can be improved.